2014
DOI: 10.1002/glia.22736
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and nestorone promote myelin regeneration in chronic demyelinating lesions of corpus callosum and cerebral cortex

Abstract: Multiple Sclerosis affects mainly women and consists in intermittent or chronic damages to the myelin sheaths, focal inflammation and axonal degeneration. Current therapies are limited to immunomodulators and anti-inflammatory drugs, but there is no efficient treatment for stimulating the endogenous capacity of myelin repair. Progesterone and synthetic progestins have been shown in animal models of demyelination to attenuate myelin loss, reduce clinical symptoms severity, modulate inflammatory responses and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 71 publications
4
63
0
Order By: Relevance
“…Thus, an exercise-dependent increase in androgen biosynthesis within the hippocampus has been shown to stimulate neurogenesis (36). Other "neurosteroids" synthesized within the CNS, such as progesterone, may also positively influence the regeneration of CNS myelin (37,38). However, in our system, the effect of AR signaling was very robust and AR inactivation was not compensated for by other promyelinating signaling mechanisms.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, an exercise-dependent increase in androgen biosynthesis within the hippocampus has been shown to stimulate neurogenesis (36). Other "neurosteroids" synthesized within the CNS, such as progesterone, may also positively influence the regeneration of CNS myelin (37,38). However, in our system, the effect of AR signaling was very robust and AR inactivation was not compensated for by other promyelinating signaling mechanisms.…”
Section: Discussionmentioning
confidence: 76%
“…This allows the recovery of neurosteroidogenesis [64]. The re-myelinating effect of progesterone is dependent on the progesterone receptor [61].…”
Section: Progesterone and Progestinsmentioning
confidence: 99%
“…In contrast, Babri et al [60] reported that intrahippocampal injection of progesterone alone or in combination with vitamin C had no improving effects on memory. Progesterone and Nestorone also decrease neuroinflammatory responses, specifically astrocyte and microglial cell activation [61]. Therefore, some progestogens are promising therapeutic candidates for promoting the regeneration of myelin.…”
Section: Progesterone and Progestinsmentioning
confidence: 99%
“…Progestogens, estrogens and androgens have indeed been shown to promote myelin regeneration in the CNS by stimulating the proliferation and differentiation of OPC and by promoting the synthesis of new myelin [9,[191][192][193][194][195]. In addition to their regenerative actions, CNS steroids exert protective effects on mature oligodendrocytes [196][197][198].…”
Section: Changes In Brain Steroid Levels In Response To Myelin Degenementioning
confidence: 99%